The ANALYSIS OF POWER FACTOR CORRECTION FOR A VOLTAGE-CONTROLLED SWITCHED BOOST INVERTERBASED PMBLDCM DRIVE (International Journal of Engineering Management Science, 2022)
This paper deals with a switched boost inverter as a single-stage power-factor-correction converter for a permanent magnet (PM) brushless dc motor (PMBLDCM) fed through a diode bridge rectifier from a single-phase ac mains. A three phase voltage-source inverter is used as an electronic commutator to operate the PMBLDCM driving an air conditioner compressor. The speed of the compressor is controlled to achieve optimum air-conditioning using a concept of the voltage control at dc link proportional to the desired speed of the PMBLDCM. The stator currents of the PMBLDCM during step change in the reference speed are controlled within the specified limits by an addition of a rate limiter in the reference dc link voltage. The proposed PMBLDCM drive PMBLDCMD) is designed and modelled, and its performance is evaluated in Matlab–Simulink environment. Simulated results are presented to demonstrate an improved power quality at ac mains of the PMBLDCMD system in a wide range of speed and input ac voltage. Test results of a developed controller are also presented to validate the design and model of the drive.